REDUCTION OF PATHOGENIC BACTERIA DURING FERMENTATION OF MASIN BY PROTEASE AND BACTERIOCIN-PRODUCING LACTIC ACID BACTERIA - Heru Pramono; Pipin Suciati; Taruna Fernando Putra; Nova Andika; Sri Utari (AQUASAINS, 2018)
Contamination of pathogenic and spoilage bacteria on fermentation process of seafood and fisheries product is a major concern on food safety. The aims of this study were isolating and applying the bacteriocin- and protease-producing lactic acid bacteria from the gastrointestinal tract of mud crab for starter culture of masin, a traditional fermented shrimp from East Java. This study consisted of characterization of lactic acid bacteria, the application on the fermentation process and microbial analysis. Ninety-four isolates were isolated from mud crab was screened for the bacteriocin and protease producing as well as characterized by pH, salinity and biochemical. Isolate IKP-29 was exhibited strong protease and bacteriocin activity. Application of Isolate IKP-29 on masin fermentation showed that sharp reduction of Escherichia coli, Vibrio sp. and lactic acid bacteria counted. This study suggested that the application of lactic acid bacteria which producing bacteriocin and protease improved the food safety of traditional fermented fish.